Հ. Հ. Դաշնակցությունը և սոցիալիզմի գաղափարը (1890—1906) - Սարգսյան, Ա. Հ. (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Партия Дашнакцутюн уже в середине 90-ых годов XIX века пропагандировала в армянской периодической печати социалистические идеи. Однако принимая идею социализма как воплощение равенства и социальной справедливости, идеологи партии вместе с тем решительно отвергали теорию классовой борьбы. The party Dashnaktsutjun already in the middle of 90-s of the XIXth c. propagandized socialist ideas in the Armenian periodical press. However admitting the idea of socialism as embodiment of equality and social justice, at the same time ideologists of the party resolutely rejected the theory of classical struggle.
Keywords: B Philosophy; Psychology; Religion; Socialism; Communism; Anarchism; B Philosophy; H Social Sciences; J Political Science; JPP Political Parties